Ethical and legal aspects of scientific research in Brazil Aspectos éticos y legales de la investigación científica en Brasil - da Silva P.R. (2010)
This article has searched and analyzed the regulatory process of the ethics of scientific research in Brazil. The methodology consisted in a systematic review, characterized by a bibliographical and documental study, results being analyzed by the content analysis technique. Legal documents studied dealt mainly with constitutional guaranties associated with scientific research, system of ethics regulation, definition of user, clinical investigations, investigations with foreign cooperation, treatment and diagnosis safeguards, human reproduction research, research with aboriginal populations, human genetics research, multicenter projects and biological data bases. It can be concluded that there are protection laws for scientific research in Brazil, establishing national priorities, determining researchers and research subjects rights and duties. There is a national system of ethics regulation established by resolutions of legislative power. Resolutions include diverse topics associated with scientific research, in line with world guidelines for research ethics, in this case the Helsinki Declaration.